Periodontitis in chronic heart failure - Fröhlich, Hanna; Herrmann, Kristina; Franke, Jennifer; Karimi, Alamara; Täger, Tobias; Cebola, Rita; Katus, Hugo; Zugck, Christian; Frankenstein, Lutz (Texas Heart Institute journal, 2016)
Periodontal disease has been associated with an increased risk of cardiovascular events. The purpose of our study was to investigate whether a correlation between periodontitis and chronic heart failure exists, as well as the nature of the underlying cause., We enrolled 71 patients (mean age, 54 ± 13 yr; 56 men) who had stable chronic heart failure; all underwent complete cardiologic and dental evaluations. The periodontal screening index was used to quantify the degree of periodontal disease. We compared the findings to those in the general population with use of data from the 4th German Dental Health Survey., Gingivitis, moderate periodontitis, and severe periodontitis were present in 17 (24%), 17 (24%), and 37 (52%) patients, respectively. Severe periodontitis was more prevalent among chronic heart failure patients than in the general population. In contrast, moderate periodontitis was more prevalent in the general population (P <0.00001). The severity of periodontal disease was not associated with the cause of chronic heart failure or the severity of heart failure symptoms. Six-minute walking distance was the only independent predictor of severe periodontitis., Periodontal disease is highly prevalent in chronic heart failure patients regardless of the cause of heart failure. Prospective trials are warranted to clarify the causal relationship between both diseases.